2022
DOI: 10.1177/00031348221142584
|View full text |Cite
|
Sign up to set email alerts
|

The Use of Whole Blood in Rural Trauma Leads to Decreased Resource Utilization

Abstract: Background Nearly 40% of trauma deaths result from uncontrolled hemorrhage. Most of these deaths occur within 24 hours, highlighting the importance of early resuscitation. Balanced component resuscitation has been shown to improve outcomes in hemorrhagic shock. However, hemostatic properties may then be decreased, leading to inadequate coagulopathy treatment or higher transfusion requirements. Data comparing the efficacy of component vs. whole blood (WB) resuscitation in early trauma is poor, particularly in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…Hazelton et al 26 reported less bleeding complications in patients treated with SWB vs. BCT (OR, 0.91; 95% CI, 0.91–0.91; p < 0.001). Niemann et al 57 reported more ventilator associated pneumonia and pulmonary embolism in patients treated with WB ( p = 0.005).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Hazelton et al 26 reported less bleeding complications in patients treated with SWB vs. BCT (OR, 0.91; 95% CI, 0.91–0.91; p < 0.001). Niemann et al 57 reported more ventilator associated pneumonia and pulmonary embolism in patients treated with WB ( p = 0.005).…”
Section: Resultsmentioning
confidence: 97%
“…Eighteen of 27 studies were retrospective with selection and confounding inherent in the design. Almost all studies had baseline differences including the seven prospective observational studies 21,23–27,57 . The two RCTs were mainly limited by their randomization processes, as blinding to the assigned intervention was not possible 22,48 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation